Difficult Preoperative Diagnosis of Lymphoepithelioma-Like Carcinoma of the Esophagus. Issue 8 (30th August 2019) - Okata, Tomoki; Uno, Kaname; Fujishima, Fumiyoshi; Saito, Masahiro; Jin, Xiaoyi; Hatta, Waku; Asanuma, Kiyotaka; Asano, Naoki; Koike, Tomoyuki; Imatani, Akira; Masamune, Atsushi
ABSTRACT: A 60-year-old man with a medical history of diabetes, liver cirrhosis, and distal gastrectomy was referred for further examination of a 10-mm pale-colored submucosal tumor around 40 cm from the incisors. Narrow band imaging–magnifying endoscopy revealed the lesion covered by smooth epithelium with irregular microvascular architecture in a sparse distribution. Endosonography showed an irregular-shaped hypoechoic lesion in the submucosa. With no evidence of metastases, we performed en bloc endoscopic submucosal dissection, whose specimen revealed esophageal lymphoepithelioma-like carcinoma invading up to 500 μm in the submucosa, a rare disease entity. Despite no additional treatment, he was alive without recurrence for longer than 88 months.